Review and Study of Intelligent Techniques in Emergency Vehicle Management System - Jose, Cyriac; Grace, K.S. Vijula (International Journal of Computer Sciences and Engineering, 2018)
The major problem in the transportation system is the interference of the emergency vehicle service, like fire fighting units, ambulance, and so on. When an emergency vehicle arrives on the multilane roadways, it is tough for the private vehicle’s driver to find out the correspondence of the emergency vehicle. Hence, there is a requirement of an intelligent traffic management system for effectively managing the emergency and the normal vehicles. This article surveys various research works in the field of emergency vehicle management. According to the existing works, an emergency vehicle management system is classified into six types, namely smart traffic control system, traffic timer synchronization, traffic forecasting, emergency vehicle recognition, route guidance and navigation for emergency vehicle, and dynamic path planning for emergency vehicle. Finally, an analysis is done based on the published years, techniques used, tools employed and metrics utilized in the emergency vehicle management techniques that are reviewed.